2018
DOI: 10.4274/jcrpe.0195
|View full text |Cite
|
Sign up to set email alerts
|

SLC30A8 Gene rs13266634 C/T Polymorphism in Type 1 Diabetes Children of Tamil Nadu, India

Abstract: The present study along with the meta-analysis does not show any substantial association of the rs13266634 C/T polymorphism with T1D development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Single Nucleotide Polymorphism (SNP) rs13266634 C/T is known to be responsible for the altered immune response to ZnT8. In the presence of β cell dysfunction and impaired autoimmunity, this SNP displays a susceptible role in the development of T1DM [27]. SLC30A8 genotypes were strongly associated with ZnT8 autoantibodies in T1DM.…”
Section: Slc30a8mentioning
confidence: 94%
See 1 more Smart Citation
“…Single Nucleotide Polymorphism (SNP) rs13266634 C/T is known to be responsible for the altered immune response to ZnT8. In the presence of β cell dysfunction and impaired autoimmunity, this SNP displays a susceptible role in the development of T1DM [27]. SLC30A8 genotypes were strongly associated with ZnT8 autoantibodies in T1DM.…”
Section: Slc30a8mentioning
confidence: 94%
“…During the exocytosis of insulin, frequent exposure of ZnT8 antigen occurs on glucose stimulated insulin secretion. Hence, it is supposed that ZnT8 exposure can exacerbate or trigger the production of autoantibodies against ZnT8 antigens in genetically susceptible individuals [27].…”
Section: It Activates Hyperpolarization Of Membrane Potential and Decreases The Voltage-dependentmentioning
confidence: 99%
“…Antibodies found against these elements are good markers for T1DM. [6][7][8] In India, a study on the prevalence of GAD antibody (GADA), ZnT8, and HLA and their diagnostic values in T1DM has found a low sensitivity of GADA and ZnT8. They concluded that for diagnosing T1DM, GADA is the most superior autoantibody.…”
Section: Introductionmentioning
confidence: 99%